Impact of metronidazole and amoxicillin combination on matrix metalloproteinases-1 and tissue inhibitors of matrix metalloproteinases balance in generalized aggressive periodontitis - Cifcibasi, Emine; Kantarci, Alpdogan; Badur, Selim; Issever, Halim; Cintan, Serdar (European Journal of Dentistry, 2015)
Objective: Generalized aggressive periodontitis (GAgP) is a complex periodontal disease affecting the entire dentition with a rapid destruction of the periodontium and resulting in loss of teeth. We hypothesized that better clinical healing of adjunctive use of amoxicillin plus metronidazole combination may be related to the effect of this combination therapy to restore imbalance between matrix metalloproteinases (MMP) and their tissue inhibitors (TIMP) which is associated with connective tissue and alveolar bone destruction in patients with GAgP. Materials and Methods: Twenty-eight subjects diagnosed with GAgP were recruited. Patients were randomly assigned to test or control groups. MMP-1/TIMP-1 ratio was compared between groups receiving scaling and root planning (SRP) alone (control) or in combination with amoxicillin plus metronidazole (test). Clinical periodontal variables were measured. Gingival crevicular fluid samples were obtained and analyzed for MMP-1 and TIMP-1. Measurements were taken at baseline and repeated at 3 and 6 months after therapy. Results: Total MMP-1 levels were significantly decreased in both groups (P < 0.05) at 3 and 6 months. MMP-1 concentration levels showed a similar pattern to MMP-1 total levels decreasing significantly at 3 months (P < 0.05). TIMP-1 concentration levels increased in the test group throughout the study period, while the difference did not reach statistical significance (P > 0.05). TIMP-1/MMP-1 balance was restored in test group at 6 months significantly better than the control group (P < 0.05). Conclusion: The results of this study suggest that metronidazole and amoxicillin combination as an adjunct to SRP results in better clinical healing through restoring TIMP-1/MMP-1 balance.
Keywords: Aggressive periodontitis; amoxicilline; matrix metalloproteinases-1; metronidazole; scaling and root planing; tissue inhibitors of matrix metalloproteinases-1